Estudo do escápulo-coracóide e da cartilagem sinarcual cérvico-torácica de Rhinoptera brasiliensis Müller & Henle e Rhinoptera bonasus (Mitchill) Elasmobranchii, Rhinopteridae) - Afonso,Andreia Francisco (2001)
A comparative analysis of the scapulocoracoid and cervico-thoracic synarcual cartilage of juvenile specimens of Rhinoptera brasiliensis Müller & Henle, 1841 and R. bonasus (Mitchill, 1815) was accomplished, in order to identify specific, individual and ontogenetic differences. In the scapulocoracoid, the scapular foramen and the posterodorsal fenestra is larger in R. brasiliensis. The anterior fenestra bridge is thicker and the metacondyle is thinner and longer in R. bonasus. This species also possesses a larger re-entrance between the mesocondyle and the metacondyle, as well as in the fitting region of'the synarcual cartilage, placed close to the scapular process. The individual differences are: posteroventral fenestra with variable diameter independent of the size of the specimens; scapulocoracoids, in some specimens, are more fragile even if they have been kept in the same conservation conditions. In the cervico-thoracic synarcual cartilage, the lateral stay in R. brasiliensis encloses completely the superior portion of the anteroscapular bridge. There are three more prominent condyles beside the suprascapula in R. brasiliensis, R. bonasus, however, shows a protuberance close to the suprascapula, inconspicuous and more distant from the scapular lamina. Several specimens of different size of R. bonasus show a synarcual cartilage wider in ventral view and higher in lateral view. In the majority of specimens, the number of ventral spinal foramina is higher than the dorsal ones in both species. R. bonasus has only one pair of asymmetric basal foramina, whereas R. brasiliensis possesses three or four foramina. Regarding individual differences, at least one specimen of R. bonasus exhibits a single basal foramen.